MODEL SUPERVISI YANG MEMBELAJARKAN BAGI KONSELOR SEKOLAH DAN PROFESI SEJENIS - Taufiq, Agus (Universitas Pendidikan Indonesia, 2017)
This article aims to explain the Model of Supervision of Development-Education (MSPK) as a result of literaturestudy in research on Development of Supervision Model to Improve School Counselor Professional Performance(2010). This model has empirically been proven effective in improving the professional performance of schoolcounselors and is assumed to be applied effectively in supervising professionals in other areas of assistanceOther explanations include the MSPK framework and action steps, the theoretical foundations of learning and insupervision and the role and qualifications of supervisors.